Types of accordion schools in the system of music education in Serbia - Устименко-Косоріч, Олена Анатоліївна (Pedagogy of Higher and Secondary Education, 2015)
Ustymenko-Kosorich Е. А. Types of accordion schools in the system of music education in Serbia. The article analyzes the types of accordion school in Serbia in the context of genre paradigm as part of a strong national music education system. This system is functioning on the basis of a two-level programs: education of a competent specialist for social and national purposes (amateur) and a performing musician of «High Art» by means of «generalization by genre».